Struktur Bata Situs Dingkel I, Desa Sambimaya, Kabupaten Indramayu: Kajian Bentuk dan Fungsi Berdasarkan Hasil Survei dan Ekskavasi - Nanang Saptono; Endang Widyastuti; Soni Prasetia Wibawa; Tendi Tendi (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Brick structures have been found in the Sambimaya Village, Juntinyuat District, Indramayu Regency. The structure is found on several dirt mounds in the rice field area. One of the locations is in the Dingkel Block. Preliminary excavations succeeded in uncovering the south side wall and southwest corner of the building. The research is intended to determine the form of the building and its function. The research method is through surveys and excavations. Surveys are mainly carried out through underground surveys. Based on the excavations, the wall structure, the corner of the building, and the staircase structure have been found. At the base of the structure, there is a pavement business using broken brick material. Several important artifacts have been found, namely broken pottery containers and gacuk. There are also animal bone fragments. Based on the structure and artifacts found, it is estimated that the building consists of at least three units and functions as a profane building.